MEMBANGUN KARAKTER KREATIF PADA PESERTA DIDIK MELALUI KEGIATAN GALERI KAMPUS (RAGAM RASA DAN KERAJINAN) - Firqah Muawwidzati; A.Mutiatul Awaliah; Andi Agus Nandi; Andi Ayu Lestari; Annisa Citra Suciawana; Auni Batrisyiah A; Muliana MS; Hasnawati; Hairul Syarifuddin; Iga Ayu Mawarni; Tarman M Arief (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This project aims to enhance the knowledge and skills of sixth-grade students at SDI Kampus IKIP and fifth-grade students at SD Inpres Hartaco Indah regarding environmentally friendly practices and cultural preservation through the creation of traditional beverages and creative artworks. The students are introduced to the process of making *Sarabba’*, a traditional Makassar drink, as well as ice cream from purple sweet potatoes. Additionally, they learn to create soap flowers, *bosara* (traditional containers) from recycled cardboard, and wall decorations from used ice cream sticks. The training covers material preparation, processing, and finishing stages, emphasizing both cultural and environmental values. After the training, students are given the opportunity to explore their interests by choosing specific skills. For example, those inclined toward carving can create soap flowers, while those interested in calculations or measurements can design *bosara* and wall decorations. The finished products will be showcased at a campus exhibition attended by supervising lecturers, mentor teachers, and fellow participants of the 2024 PPG Prajabatan Cohort 1 program. The project not only aims to foster students’ creative abilities but also to raise awareness about the importance of cultural preservation and environmental stewardship. By integrating art, culture, and ecological learning, this project offers students valuable experiences in understanding and appreciating art while contributing to environmental sustainability.